The Influence of Green Innovation on Financial Performance Moderated by Chief Executive Officer Characteristics - Putri Nugraheni, Deya Leony (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of green innovation on financial performance with the characteristics of the Chief Executive Officer (CEO) as a moderating variable in coal companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2024 period. Green innovation in this study consists of green product innovation and green process innovation. The research was conducted on 170 coal companies using a quantitative approach. The results show that both green product innovation and green process innovation have a positive effect on financial performance. However, CEO characteristics demonstrate different moderating roles. CEO education does not moderate the relationship between green product innovation and financial performance but does moderate the relationship between green process innovation and financial performance. Similarly, CEO experience does not moderate the relationship between green product innovation and financial performance but does moderate the relationship between green process innovation and financial performance. These findings emphasize that CEO characteristics, particularly education and experience, play a more significant role in strengthening the impact of green process innovation on improving company financial performance.